Perkembangan Sistem Peradilan Pidana Di Indonesia - Gani Hamaminata (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
The Criminal Justice System outlined by the 1981 Criminal Procedure Code is an Integrated Criminal Justice System that is based on the principle of "functional differentiation" between law enforcement officials/agencies in accordance with the "stage of the process of authority" granted by the law. The Integrated Criminal Justice System is a system in criminal justice that becomes a reference for the implementation of a fair trial and as expected by the wider community. In the criminal justice system, there are things that must be synchronized in order to achieve a truly integrated system, namely substance, structural and cultural synchronization. Keywords : Criminal Justice System and Criminal Procedure Code